Genetic Variability and Association of Various Heat Stress Relevantindices for Selecting Heat Tolerant Chickpea (Cicer arietinum L.) Genotype - Jha, Uday Chand; Kole, Paresh Chandra; Singh, Narendra Pratap; Shil, Sandip; Gawande, Dhananjay (International Journal of Bio-resource and Stress Management, 2017)
Given the global climate change and frequent episodes of heat stress (HS), global crops including chickpea are receiving serious challenge of yield loss across the globe.A wide range of genetic variability for various phenological traits and yield related traits were recordedin 42 chickpea genotypes including two checks under both normal and HS sown conditions. Aiming at selection of superior genotype and to estimate yield loss, various HS indices were calculated and their significant association analyses were worked out based on the plot yield performance of the given genotypes under both conditions. Based on the results of evaluated stress indices, YI and MP could be deployed to select superior HS tolerant genotypes. In parallel, principal component analysis (PCA) reduced all the calculated HS tolerance indices into two major components; PCA1 explained 57.6% and PCA2 explained 41.6% of the total variation. Moreover, cluster analysis grouped all the genotypes into distinct 4 groups. Thus, a comprehensive assessment of genetic variability and screening of HS tolerant genotype recruiting various selection indices could hasten development of HS tolerant chickpea variety.